2019
DOI: 10.3390/ani9070432
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in SLC5A1, CCNA1, and ABCC1 and the Association with Litter Size in Small-Tail Han Sheep

Abstract: SLC5A1, CCNA1, and ABCC1 have been extensively studied as candidate genes because of their great influence on the reproductive traits of animals. However, little is known about the association between polymorphisms of the SLC5A1, CCNA1, and ABCC1 genes and litter size in Small-Tail Han sheep. In this study, the expression levels of SLC5A1, CCNA1, and ABCC1 in HPG (hypothalamic–pituitary–gonadal) axis tissues of polytocous and monotocous Small-Tail Han sheep were analyzed by qPCR. To better understand the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…With the development of modern breeding technology and breeding industry, we wanted to explore a useful and efficient way to promote goat growth traits and enhance economic performance. Many studies have confirmed that polymorphisms of some candidate genes could be associated with economic traits in livestock [5][6][7]. Van Laere found that a G to A nucleotide mutation appeared in intron 3 of porcine IGF2, which abolishes BED-type containing 6 repressor (a kind of transcription factor) binding and affected pig meat production [8].…”
Section: Introductionmentioning
confidence: 98%
“…With the development of modern breeding technology and breeding industry, we wanted to explore a useful and efficient way to promote goat growth traits and enhance economic performance. Many studies have confirmed that polymorphisms of some candidate genes could be associated with economic traits in livestock [5][6][7]. Van Laere found that a G to A nucleotide mutation appeared in intron 3 of porcine IGF2, which abolishes BED-type containing 6 repressor (a kind of transcription factor) binding and affected pig meat production [8].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, to establish optimal breeding programs, plenty of candidate genes, as well as their genetic variations should be appropriately used [4][5][6][7]. Maker-assisted selection (MAS) can satisfy the need to screen crucial genes and consider the relation between their polymorphisms and growth-related traits [8][9][10][11]. Herein, establishing a MAS system and performing candidate genes analyses will speed up the development of goat breeding [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the candidate genes in ROH, associated with the "Oxytocin signaling pathway" and "Calcium signaling pathway" metabolic pathways, is the ITPR1 (Inositol 1,4,5-trisphosphate receptor Type 1) gene. It contributes to endocrine control [62] and acts on GnRH, estrogen, oxytocin, and TGF-beta signaling pathways [63]. The CACNB2 (Calcium Voltage-Gated Channel Auxiliary Subunit Beta 2) gene is associated to ion channel function, which acts on uterine contraction during labor in humans [64].…”
Section: Functional Annotation Of Roh In Prolific Sheepmentioning
confidence: 99%